Mostly Sunny: A Forecast of Tomorrow's Power Index Research - Sascha Kurz; Nicola Maaser; Stefan Napel; Matthias Weber (Tinbergen Institute, 2014)
wer index research has been a very active field in the last decades. Will this continue or are all the important questions solved? We argue that there are still many opportunities to conduct useful research with and on power indices. Positive and normative questions keep calling for theoretical and empirical attention. Technical and technological improvements are likely to boost applicability
Keywords: B40; D71; D72; 330; power index analysis; economic perspectives and methodology; committee voting; optimal voting rule